2011
DOI: 10.1007/s10495-011-0675-0
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut

Abstract: Although several features of apoptosis and autophagy have been reported in the larval organs of Lepidoptera during metamorphosis, solid experimental evidence for autophagy is still lacking. Moreover, the role of the two processes and the nature of their relationship are still cryptic. In this study, we perform a cellular, biochemical and molecular analysis of the degeneration process that occurs in the larval midgut of Bombyx mori during larval-adult transformation, with the aim to analyze autophagy and apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
168
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 83 publications
(122 reference statements)
8
168
1
4
Order By: Relevance
“…31 In a previous study, we have found that autophagy precedes apoptosis in the midgut during Bombyx metamorphosis, but the core mechanism is not illustrated. 40 Here, we found that starvation and 20E addition caused significant cell death after 4 to 16 h treatment, with autophagy proceeding apoptosis at least by 3 h in Bombyx Bm-12 cells (Figs. 1 to 4), which was similar to the observation in midgut during metamorphosis.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…31 In a previous study, we have found that autophagy precedes apoptosis in the midgut during Bombyx metamorphosis, but the core mechanism is not illustrated. 40 Here, we found that starvation and 20E addition caused significant cell death after 4 to 16 h treatment, with autophagy proceeding apoptosis at least by 3 h in Bombyx Bm-12 cells (Figs. 1 to 4), which was similar to the observation in midgut during metamorphosis.…”
Section: Discussionmentioning
confidence: 56%
“…28,29,39 Importantly, we found that autophagy precedes apoptosis in the midgut. 40 In this study, we discovered that being cleaved into BmATG5-tN and BmATG6-C, BmATG5 and BmATG6 mediate apoptosis following autophagy induced by 20E or starvation in Bombyx Bm-12 cells, reflecting that autophagy precedes apoptosis in the midgut during Bombyx metamorphosis.…”
Section: Basic Research Papermentioning
confidence: 78%
See 2 more Smart Citations
“…However, other potential mechanisms which might be involved in the maintenance of homeostasis in invertebrates, such as apoptosis, self-regeneration of tissues and organs, accumulation of spherites, synthesis of methallothioneins or antioxidants (Parthasarathy and Palli, 2007;Park and Takeda, 2008;Hakim et al, 2010;Rost-Roszkowska et al, 2010a, 2010bChajec et al, 2012), have been studied only in some tardigrade species (Rebecchi et al, 2009a;Rizzo et al, 2010;Bonifacio et al, 2012). In many invertebrates the regenerative properties of the midgut epithelium are also considered as adaptive mechanisms for coping with external stress factors (Wilczek, 2005;Tettamanti et al, 2007;Park and Takeda, 2008;Malagoli et al, 2010;Rost-Roszkowska et al, 2011b;Franzetti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%